2021
DOI: 10.3892/ijmm.2021.4969
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA‑375‑3p‑mediated regulation in tinnitus development

Abstract: changes in the dorsal cochlear nucleus (dcN) following exposure to noise play an important role in the development of tinnitus. As the development of several diseases is known to be associated with microRNAs (miRNAs/miRs), the aim of the present study was to identify the miRNAs that may be implicated in pathogenic changes in the dcN, resulting in tinnitus. A previously developed tinnitus animal model was used for this study. The study consisted of four stages, including identification of candidate miRNAs invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…A previous study indicated the downregulation of miR-375-3p in rats with tinnitus and that overexpressing miR-375-3p may prevent the persistence of tinnitus in rats. 21 In this study, we further explored the function of miR-375-3p in regulating salicylate-triggered neuron injury. Consistent with previous evidence, our results depicted that miR-375-3p level was decreased in salicylate-treated SH-SY5Y neurons in comparison to that in control cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study indicated the downregulation of miR-375-3p in rats with tinnitus and that overexpressing miR-375-3p may prevent the persistence of tinnitus in rats. 21 In this study, we further explored the function of miR-375-3p in regulating salicylate-triggered neuron injury. Consistent with previous evidence, our results depicted that miR-375-3p level was decreased in salicylate-treated SH-SY5Y neurons in comparison to that in control cells.…”
Section: Discussionmentioning
confidence: 99%
“…20 Moreover, Han et al proposed that miR-375-3p is downregulated in rats with tinnitus compared with that in control rats and overexpressing miR-375-3p may prevent the persistence of tinnitus in rats. 21 Nonetheless, the molecular mechanisms of miR-375-3p underlying tinnitus pathogenesis remain unclarified.…”
Section: Introductionmentioning
confidence: 99%
“…Hearing levels were estimated using auditory brainstem response (ABR) thresholds. Two months after noise exposure, all rats were euthanized and the cochleae and CN were dissected [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cochlear nucleus is the first center in the auditory pathway that processes acoustic signals from direct projections of the auditory nerve. In addition to cellular changes, changes at the molecular levels could be responsible for the pathophysiology of tinnitus [17][18][19] . Y. ÜSTÜNDAĞ, G. DİNÇ, R. BAL In the last decade, animal research has clearly demonstrated that tinnitus is a pathology of synaptic plasticity 20 .…”
Section: Introductionmentioning
confidence: 99%